The Spanish Lexical Availability of Secondary and High School Students: Incidence of the Sex Variable - Herranz-Llácer, Cristina V. (2024)
The aim of this article is to investigate the impact of the variable sex on the available lexicon of 184 students from 1st year of secondary school and 1st year of high school, and to analyse whether there are differences in the number of words and their usage between males and females. The study utilized the Lexical Availability Index (LAI), Compatibility Index (CI), and the Percentage of Retained Lexical Availability (PRLA) across eight interest areas (five traditional and three novel). The data collection and analysis revealed differences between the two repertoires. The main conclusion highlights the existence of differentiated vocabulary usage in certain areas.